2012
DOI: 10.3109/10826084.2011.629709
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Alcohol Dependence and Their Effect on Sexual Behavior Change

Abstract: This study utilized data from a National Institute on Drug Abuse and National Institute on Alcohol Abuse and Alcoholism funded community-based HIV prevention program in the Midwest in 2000. We categorized women who met lifetime criteria for alcohol dependence (using the DIS) and who also had used cocaine (n = 324) into four alcohol typologies based on onset of regular drinking and the length of time to dependence. The Risk Behavior Assessment measured sex behaviors, combined into a risk index, before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The effects of alcohol on the appraisal of sexual potential differed by partner risk condition. Some results have suggested that wives of alcoholic men are unknowingly placed at risk for indirect exposure to STIs as a result of their husbands' sexual risk behaviors (Hall, Fals-Stewart, & Fincham, 2008;Osborne & Cottler, 2012;Varma, Chandra, Callahan, Reich, & Cottler, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of alcohol on the appraisal of sexual potential differed by partner risk condition. Some results have suggested that wives of alcoholic men are unknowingly placed at risk for indirect exposure to STIs as a result of their husbands' sexual risk behaviors (Hall, Fals-Stewart, & Fincham, 2008;Osborne & Cottler, 2012;Varma, Chandra, Callahan, Reich, & Cottler, 2010).…”
Section: Discussionmentioning
confidence: 99%